Kepatuhan Perawat dalam Melakukan Dokumentasi Asuhan Keperawatan - Ni Kadek Erna; Ni Luh Putu Thrisna Dewi (Holistic Nursing and Health Science, 2020)
Introduction: Nurses' lack of understanding and non-compliance in nursing documentation resulted in low quality of documentation and nursing services. One of factors which affects nursing documentation is self-efficacy. The purpose of this study was to know the correlation of self-efficacy and the compliance of nurses in the nursing documentation. Methods: This research used cross-sectional design with the descriptive documentation approach. The sample of the study was 23 nurses in a hospital recruiting with a nonprobability technique type i.e. total sampling. The inclusion criteria in this study were nurses who were willing to be respondents and had at least a diploma in nursing education. The instrument used was a self-efficacy questionnaire and the nursing care documentation compliance observation sheet. Data analysis used Rank Spearman test with the meaning level 0.05. Results: Most of nurses had high self-efficacy (69.9%) and majority nurse obey in nursing care documentation (73.9%). The statistic test showed p value = 0.000 < (0.05) with r = 0.898. Conclusion: This result confirmed that there is a relation between self-efficacy and the compliance of nurses in nursing documentation at hospital.